Development of Basics and Learning Process Biology Textbooks Based on the Industrial Revolution 4.0 - Jodion Siburian; Ali Sadikin (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to develop a basic textbook and biology learning process based on the industrial revolution 4.0. The research method uses R&D with the ADDIE model (analysis, design, development, implementation and evaluation). The research results show that the need for basic textbooks and a biology learning process based on revolution 4.0 is very high. The design of this book uses A5 size paper, with a table of contents including: learning in the era of the industrial revolution 4.0, biology learning methods, teaching skills, learning media, current biology learning models and teaching aids. At the development stage, the book Basics and Biology Learning Process Based on the Industrial Revolution 4.0 was declared feasible by the validator. At the implementation stage, this book received a good rating (82.25) in small group trials and good (84.3) in large group trials. Conclusion, basic books and the biology learning process are in the appropriate category according to the validator's assessment and the good category according to the lecturer's and student's assessment.